Intravenous Haloperidol versus Midazolam in Management of Conversion Disorder; a Randomized Clinical Trial - Jafari, Mohammadali; Aliheidari Biuki, Amir; Hajimaghsoudi, Majid; Bagherabadi, Mehdi; Zarepur, Ehsan (Archives of Academic Emergency Medicine, 2018)
Introduction: Conversion disorder is a condition in which the patient shows psychological stress in physical ways. This study aimed to compare the effects of haloperidol versus midazolam in patients with conversion disorder. Methods: This double-blind randomized clinical trial was conducted on patients with conversion disorder who had presented to the emergency department, throughout 2015. Patients were randomly divided into two groups and were either treated with 2.5 mg of intravenous (IV) haloperidol or 2.5 mg of IV midazolam. Recovery rate, time to recovery, and side effects of both drugs 1 hour, 24 hours, and 1 week after treatment were compared using SPSS19. Results: 140 patients were divided into two groups of 70. There were no significant differences between the groups regarding the baseline characteristics. 12 (17.1%) patients who were treated with IV haloperidol experienced drug side effects within 1 hour and 12 (17.1%) within 24 hours, while only 3 (4.3%) patients in IV midazolam experienced side-effects within 1 hour after drug administration (p = 0.026). The symptoms of the disease subsided in 45 (success rate: 64.3%) patients in midazolam and in 64 (success rate: 91.5%) participants in haloperidol group (P<0.001). Mean recovery time was 31.24 ± 7.03 minutes in IV midazolam and 30.53 ± 7.11 minutes in IV haloperidol group (p = 0.592). Absolute risk reduction (ARR) of treating patients with haloperidol compared to midazolam is about 27%. Conclusion: The response of patients to treatment with haloperidol is clearly better than midazolam. Although more transient and minor side-effects were observed in the group treated with haloperidol compared to midazolam group, serious side-effects were rare for both treatments.